Pemberdayaan Masyarakat Melalui Pengolahan Jagung Di Desa Botubilotahu Kecamatan Marisa Kabupaten Pohuwato - Hasan, Wahyudin; Hanapi, Yayan; Mayang, Faqih Al-Ghazali T.; Kumay, Asmaranda; Dunggio, Sabrina; Belembele, Moh. Dimas; Syamsudin, Febriyanto; Wowor, Muhammad Rinaldy; Towana, Putriyanti; Sado, Deysi Ramadani P.; Pongoalo, Melisa Andriayanti; Datuela, Detasya; Palowa, Fidya H. (Lembaga Dongan Dosen, 2024)
Corn is one of Indonesia's leading food crops with great potential, both as a food source and a functional product. In Botubilotahu Village, Marisa District, Pohuwato Regency, most corn is still sold in raw form, even though corn can be processed into various products, one of which is corn chips. Although corn chips are already known, their distribution is limited to a local scale. The Community Service Program in this village aims to empower the community, especially housewives, by utilizing corn to make corn chips as a healthy snack alternative. This program involves socialization, training, and product marketing, with the necessary equipment and raw materials provided. It is hoped that processing corn into chips can increase the selling value of corn and improve the welfare of the local community